Bedeutung der Radioonkologie beim Plasmozytom oder multiplen Myelom - König, Laila; Herfarth, Klaus (Der Onkologe, 2018)
Treatment options for patients with plasmacytoma or multiple myeloma should be discussed in an interdisciplinary context. This systematic review focusses on the importance of radiotherapy in multiple myeloma and plasmacytoma.
Gesehen am 03.12.2019